Effort-Reward Imbalance Is Associated With Alcohol-Related Problems. WIRUS-Screening Study - Skogen, Jens Christoffer; Thørrisen, Mikkel Magnus; Bonsaksen, Tore; Vahtera, Jussi; Sivertsen, Børge; Aas, Randi Wågø (Frontiers in Psychology, 2019)
There is ample evidence of associations between a perceived stressful working environment and several health-related outcomes. To better understand potential mechanisms behind these observations some studies have focused on the relationship between effort-reward imbalance at work and alcohol consumption. So far, the findings have been inconsistent. One reason for this inconsistency might come from the focus on alcohol consumption per se, while disregarding other aspects such as adverse consequences related to the consumption of alcohol. The aim of the present study was to explore associations between perceived effort and reward, effort-reward imbalance and overcommitment, and alcohol-related problems. Using data from the alcohol screening component in the Norwegian WIRUS-project (N=5,080), we ascertained the perceived effort, reward, effort-reward imbalance (ERI) and overcommitment using the effort-reward imbalance questionnaire. Alcohol-related problems was determined using a cut-off ≥8 on the Alcohol Use Disorder Identification Test (AUDIT). Associations were estimated using crude and adjusted logistic regression models. Covariates were age, gender and education. We found associations between different aspects of ERI and overcommitment, and alcohol-related problems. Specifically, the main analysis indicated that there was an increased odds for alcohol-related problems among those who reported high levels of ERI in conjunction with high overcommitment (adjusted OR: 1.40 (CI95%1.10-1.78)) compared to those with low levels of ERI and low overcommitment. Our findings suggest that ERI and overcommitment is associated with increased likelihood of alcohol-related problems. These findings indicate that individual and work-related factors should be taken into account collectively when aiming to determine the impact of psychosocial work environment on alcohol-related problems. Due to the cross-sectional nature of the present study, we are not able to determine the direction of the associations, and future studies should aim to investigate this.